'Tianxia' and 'Renlei mingyun gongtongti': a revival of cosmopolitanism in a Chinese cultural disguise?. Issue 1 (2nd January 2021) - Ouyang, Xiao
ABSTRACT: Tianxia and renlei mingyun gongtongti are two Chinese concepts that are of significance for reflecting on 'China and Global Development.' Both present a revival of cosmopolitanism in China, while accompanied by a calling for Chinese rejuvenation. In defining cosmopolitanism in terms of two intrinsic conditions – common community and universal equality – I argue that cosmopolitanism rooted in the Chinese philosophical tradition may provide a distinct solution to the equality condition from the Western liberal-individualist ones. I propose the notion of Confucian relational equality. There is indeed 'inequality' for the roles in a relation, in the sense that obligations and norms of conduct are defined differently and accomplished codependently. However, ideally, all full-fledged person-ings (understood as life stories in a society in a given historical period) are constituted by a dynamic and unfolding manifold of always specific relations concretized by various social roles, and usually do bear a comparable amount of functionally equivalent primary roles. As roles co-emerge among person-ings, relational equality is only possible when roles are continuously generated and sustained by transmission, which entails that community with a history, rather than an abstract and ontological individual, is a prerequisite.